Student abstract: Mwangolo Kombo Shaibu - Mwangolo, Kombo Shaibu (UoEm, 2024)
Mwangolo Kombo Shaibu, a fourth-year law student of the University of Embu wins the first position with a cash prize award of CHF 450, in the essay writing competition of the 21st Century, organized by the International Committee of the Red Cross.